The shape of the human adult trachea among Bangladeshi males - Yousuf, BM Ali; Begum, K; Shamim, KM (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: trachea; cross-sectional shape; endotracheal; CT scan doi: 10.3329/jcmcta.v18i2.3832 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):26-27